1996
DOI: 10.1021/jf960168x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sample Preparation Method on Birch (Betula pendula Roth) Leaf Phenolics

Abstract: Sample preparation methods for high-performance liquid chromatographic analysis of birch leaf phenolics were compared. The methods tested were:  (1) air-drying at ambient temperature, (2) oven-drying at 40 °C, (3) oven-drying at 80 °C, (4) freeze-drying, prefreezing with liquid N2, (5) freeze-drying, prefreezing at −18 °C, (6) freeze-drying without prefreezing, (7) storing frozen for 12 days without drying, and (8) immediate extraction of fresh samples. Although there were significant differences among methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 11 publications
4
49
1
1
Order By: Relevance
“…The drying method did not dramatically change the relative phenolic profile of birch (Betula pendula Roth) leaf, but the ethanol extraction of fresh plant best preserved the phenolic concentration of the crude plant (Keinanen and Julkunen, 1996). Of the various drying methods tested, freeze-drying of a slowly frozen (as opposed to flash-frozen) leaf preserved most of the phenolics.…”
Section: Polyphenolsmentioning
confidence: 99%
“…The drying method did not dramatically change the relative phenolic profile of birch (Betula pendula Roth) leaf, but the ethanol extraction of fresh plant best preserved the phenolic concentration of the crude plant (Keinanen and Julkunen, 1996). Of the various drying methods tested, freeze-drying of a slowly frozen (as opposed to flash-frozen) leaf preserved most of the phenolics.…”
Section: Polyphenolsmentioning
confidence: 99%
“…In another study, Keinanen and Julkunen-Tiitto showed that quantity of phenolic compounds extracted from birch leaves (Betula pendula Roth) were affected by the sample drying procedure. 40 The authors compared the influence of eight different sample drying conditions (air drying at ambient temperature, oven-drying at 40 • C, oven-drying at 80 • C, freezedrying after pre-freezing samples with liquid N 2 , freeze-drying after pre-freezing samples at −18 • C, freeze-drying without pre-freezing samples, storing frozen samples for 12 days without drying, and immediate extraction of fresh samples) on extraction of phenolic compounds from birch leaves. The authors recommended that for quantitative analysis samples should be immediately analyzed after collection.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The authors recommended that for quantitative analysis samples should be immediately analyzed after collection. Among the drying procedures, highest concentrations of phenolics were obtained with freeze-drying samples after pre-freezing at −18 • C. 40 Malovana et al compared liquid-liquid extraction with solid-phase extraction of phenolic compounds from wine samples. 41 The authors observed that sample preparation with liquid-liquid extraction using diethyl ether as extraction solvent at pH 2.0 provided optimum extraction yields of the phenolic compounds.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The drying at low temperatures protects against the degradation of the active constituents, but it is slow and metabolic processes may continue longer, which may lead to quality loss of the aromatic plants and subsequently of the produced added value products (Keinänen & Julkunen-Tiitto 1996). Many drying methods such as convection oven drying, freeze-drying, microwave drying etc.…”
mentioning
confidence: 99%